Enhancing Pedagogical Approaches in Maritime Cadet Management Studies: Insights from STIP Jakarta Graduates - Mudakir Mudakir (Dinasti International Journal of Education Management And Social Science, 2024)
This qualitative study examines pedagogical strategies in maritime cadet management studies at Sekolah Tinggi Ilmu Pelayaran Jakarta (STIP Jakarta). Through interviews and document analysis, researchers explore how STIP Jakarta aligns with international standards, fosters professionalism, and meets industry needs. Findings reveal a curriculum emphasizing practical application and interdisciplinary learning, complemented by adherence to international regulations and guidelines. Experiential learning and industry immersion nurture professionalism, while emphasis on teamwork and communication prepares graduates for the maritime sector. The research underscores the importance of effective pedagogy in preparing graduates for successful careers and contributes to ongoing discourse on education management and social science.